2006
DOI: 10.1097/01.ccm.0000242755.74063.ed
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of capillary leakage by hydroxyethyl starch (130/0.42) in a porcine model of septic shock

Abstract: In this porcine septic shock model, HES 130/0.42 attenuated capillary leakage significantly more effectively than HES 200/0.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
3
29
0
2
Order By: Relevance
“…Immediately after baseline data collection, peritonitis was induced, and simultaneously animals were randomly assigned either to FiO 2 ϭ 0.21 (control group, n ϭ 10, 7 males/3 females, median body weight 51 [range 46 -59] kg), which was only modified thereafter to maintain arterial hemoglobin oxygen saturation Ն90%, or to 100% oxygen (hyperoxia group, n ϭ 10, 4 males/6 females, median body weight 51 [range 46 -58] kg), which was maintained until the end of the experiment. In accordance with literature reports (28,29) and pilot experiments, fecal peritonitis was induced by inoculating the autologous feces into the abdominal cavity through the drainage tubes, which were subsequently kept clamped for the following 12 hrs. Additional measurements were recorded at 12, 18, and 24 hrs of peritonitis.…”
Section: Methodsmentioning
confidence: 89%
“…Immediately after baseline data collection, peritonitis was induced, and simultaneously animals were randomly assigned either to FiO 2 ϭ 0.21 (control group, n ϭ 10, 7 males/3 females, median body weight 51 [range 46 -59] kg), which was only modified thereafter to maintain arterial hemoglobin oxygen saturation Ն90%, or to 100% oxygen (hyperoxia group, n ϭ 10, 4 males/6 females, median body weight 51 [range 46 -58] kg), which was maintained until the end of the experiment. In accordance with literature reports (28,29) and pilot experiments, fecal peritonitis was induced by inoculating the autologous feces into the abdominal cavity through the drainage tubes, which were subsequently kept clamped for the following 12 hrs. Additional measurements were recorded at 12, 18, and 24 hrs of peritonitis.…”
Section: Methodsmentioning
confidence: 89%
“…Investigating the effects of HES 130/0.42 and HES 200/0.5, we demonstrated that it was possible in our porcine septic shock model to significantly attenuate systemic capillary leakage by HES 130/0.42 in comparison to HES 200/0.5 [33] (Fig. 2).…”
Section: Fluid Resuscitation In Experimental Sepsismentioning
confidence: 82%
“…P e 0.05 versus control group; # p e 0.05 HES 200/0.5 versus HES 130/0.42. From [33] with permission solutions were similar effective in maintaining systemic hemodynamics and oxygenation. Attenuation of systemic capillary leakage is in line with a higher plasma volume and a less pronounced positive fluid balance in the HES 130/0.42 group compared to the HES 200/0.5 group, although it needs to be stressed that the latter two differences were not statistically significant.…”
Section: Fluid Resuscitation In Experimental Sepsismentioning
confidence: 88%
See 1 more Smart Citation
“…There is some experimental evidence suggesting differences between HES 130 and HES 200 [29], but this remains to be tested adequately in powered long-term (90-day) clinical studies.…”
Section: Hydroxyethyl Starch (Hes)mentioning
confidence: 95%